Penyelesaian Sengketa Konsumen Di Indonesia - Amin, Muhammad Nur; Deshaini, Liza; Sudarna, Sudarna (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Settlement of consumer disputes in the General Courts is by filing lawsuits and examining evidence in court while settlement of consumer disputes outside the Court is by settlement of immediate (direct) compensation by peaceful means and claims for compensation through the Consumer Dispute Settlement Agency (BPSK).